A142 CLINICAL AND RADIOLOGIC PREDICTORS OF RESPONSE TO ANTI-TNF ALPHA THERAPY IN PATIENTS WITH PERIANAL CROHN’S DISEASE. - Parlow, S (J Can Assoc Gastroenterol, 2018)
BACKGROUND: Perianal fistulas are a frequent manifestation of Crohn’s Disease (CD) and often result in substantial morbidity. Pelvic magnetic resonance imaging (MRI) is commonly performed prior to initiating therapy to evaluate fistula anatomy, and the presence of complications. These factors are critical for determining if therapy can be safely initiated. Although anti Tumor Necrosis Factor alpha (anti-TNF) therapy has emerged as the most effective treatment for perianal CD (PCD), a substantial proportion of patients who receive this therapy will not achieve clinical remission. AIMS: The aim of this study is to determine clinical and radiologic factors associated with clinical remission in patients with PCD. METHODS: A retrospective, observational study was performed between 2005–2016. Patients with PCD who underwent a pelvic MRI were identified by a search of our institutional electronic picture archiving and communication system (WEB PACS). Study inclusion criteria included: patients over the age of 18 with PCD who underwent a pelvic MRI within 12 months of starting anti-TNF therapy. Clinical remission, defined as a lack of fistula drainage without clinical evidence of abscess, was assessed at 3 months after initiating therapy. A single, experienced radiologist reinterpreted each MRI study using a standardized template. Clinical and radiologic factors were selected a priori and were compared among patients with and without clinical remission. Chi square, Wilcoxon Score and Fisher exact tests were used to compare variables where appropriate. RESULTS: Seventy-seven patients met our inclusion criteria. Twenty-five (32.5%) patients achieved clinical remission at 3 months and fifty-two (67.5%) did not. Age, gender, and smoking status were similar between both groups of patients, as were age of diagnosis, Montreal Classification of disease characteristics, and duration of disease. Patients who did not achieve remission required more examinations under anesthesia (OR 2.4; p=0.076), and received a higher number of setons (p=0.063) prior to initiation of anti-TNF therapy. Patients who did not achieve remission were also more likely to have multiple primary fistula tracts (OR 4.8; p=0.035), multiple liquid containing tracts (OR 2.57; p=0.06), and a greater number of primary enhancing tracts (p=0.047) seen on MRI. CONCLUSIONS: Multiple radiologic features are associated with a lack of clinical remission in patients with PCD and may help in patient counselling, and to determine which patients should be treated aggressively. FUNDING AGENCIES: None